Hydraulic Modeling of a Water Distribution Network in a Tourism Area with Highly Varying Characteristics. (2016) - Kara, Selami; Karadirek, I. Ethem; Muhammetoglu, Ayse; Muhammetoglu, Habib
Abstract: Hydraulic models are efficient decision support tools for effective management of water distribution networks (WDNs). This study presents an EPANET hydraulic model application at Old Town DMA (District Metered Area), a well-known tourism area in Antalya City, Turkey. Old Town DMA has highly variable WDN characteristics and it contains about 1400 active and inactive water subscribers, mostly related to tourism facilities. Daily and hourly water consumption profiles and water consumption rates by different subscribers in the DMA exhibit wide variations. The temporal and spatial variations of water consumptions and highly varying topographic levels of the DMA are taken into account to allocate nodal water demand in hydraulic modeling. Water pressure and flow rates are continuously monitored online at the SCADA station located at the entrance of the DMA. Additionally, continuous water pressure measurements are performed via portable pressure loggers at 4 different points located at different elevations of the DMA. The monthly water consumption of each water subscriber is recorded. Moreover, the daily and hourly water consumption rates of 13 different water subscribers were monitored for 5 days. The obtained data sets were used to prepare water consumption patterns for different water subscribers and to estimate nodal demands. The hydraulic model was calibrated for Hazen - Williams pipe roughness coefficient and the predicted pressure values were in good agreement with field measurements.